(untitled) (Konferensiyalar | Conferences, 2024)
In today’s interconnected world, the demand for language learning is growing. The purpose of this article is to analyze a variety of e-learning advantages in the language acquisition. In addition, it explores the teaching methodology and potential barriers associated with distance language learning.